Advanced reliability analysis of Polymer Electrolyte Membrane Fuel Cells using Petri-Net analysis and fuel cell modelling techniques. (21st September 2015) - Whiteley, Michael; Fly, Ashley; Leigh, Johanna; Dunnett, Sarah; Jackson, Lisa
Abstract: Reliability issues with fuel cells have held back the commercialisation of this new technology, and as such are required to be studied further. Current reliability standards for automotive applications require an operational lifetime of 150, 000 miles or 5000 h. These standards are hard to achieve; therefore in depth reliability analysis and degradation studies can help allude towards the key areas of improvement in fuel cell technology to meet these standards. Previous Failure Mode and Effect Analysis (FMEA) work has shown that the multi-component system of a Polymer Electrolyte Membrane Fuel Cell (PEMFC) is inherently complex. Dependencies exist between multiple failure modes which discounts Fault Tree Analysis (FTA) as a feasible reliability modelling technique. Therefore, in this study, Petri-Net simulation and fuel cell modelling techniques have been adopted to develop an accurate degradation model. Operational parameters such as water content, temperature and current density and their effects on the occurrence of failure modes can be modelled through this technique. The work will improve previous fuel cell reliability studies by taking into consideration; operating parameters (water content, temperature), fuel cell voltage based on demand (drive cycles) and dependencies between failure modes. Highlights: Novel method to ascertain lifetime performance of PEMFCs. Uses verified performance model of PEMFC with degradation simulation extension. Fully integrated interaction between failure modes. Output of failures directly affects input parameters to fuel cell model.